134k views
3 votes
-5/3 is a root of f(x) = (3x + 5) (x2 - 6x + 9)2 = 0 True False

User Monae
by
4.9k points

2 Answers

3 votes
false...................
User Hmunoz
by
4.5k points
5 votes

For this case we have the following function:


f (x) = (3x + 5) (x ^ 2-6x + 9) ^ 2

To find the roots we must equal the function to 0, that is:


(3x + 5) (x ^ 2-6x + 9) ^ 2 = 0

So:


3x + 5 = 0

Subtracting 5 from both sides:


3x = -5

Dividing between 3 on both sides:


x = - \frac {5} {3}

Thus, one of the roots is
x = - \frac {5} {3}

Answer:

True

User Glinkot
by
5.1k points